PENENTUAN Streptococcus Group A PENYEBAB FARINGITIS PADA ANAK MENGGUNAKAN McIsaac SCORE DAN RAPID ANTIGEN DETECTION TEST (RADT) DALAM UPAYA PENGGUNAAN ANTIBIOTIKA SECARA BIJAK - Dewi, AA Agustia Sinta; Noviyani, Rini; Niruri, Rasmaya; Suherman, F.S.; Triyasa, I Putu (Jurnal Biologi Udayana, 2013)
Pharyngitis can be caused by viruses and bacteria. The bacteria that most commonly causes pharyngitis is Streptococcus Group A . In the treatment of pharyngitis, it is very important to ensure the cause for determining the appropriate treatments, therefore unnecessary use of antibiotics can be avoided. Antibiotics should be prescribed in patients with pharyngitis caused by bacteria. Diagnostic test that can be applied to determine the causes of pharyngitis are McIsaac score and Rapid Antigen Detection Test (RADT). The purpose of this study was to investigate the presence of Streptococcus Group A as the cause of pharyngitis applying McIsaac scores and the RADT. This study was cross-sectional. Patients with the inclusion and exclusion criteria were given an initial assessment using the McIsaac score, subsequently tested with the RADT. The results gained from the McIsaac scores and subsequent RADT were compared.  It was found that as many as 124 patients suspected of having bacterial pharyngitis. Forty two of them were scored 3; 55 patients scored 4, and  27 patients scored 5. All patients tested with the RADT, only 18 patients gave positive results. Out of those 18 patients positively tested, 6 patients scored 3; 8 patients scored 4, and 4 patients scored 5. In was concluded that the use of RADT was better than McIsaac scores in determining pharyngitis caused by Streptococcus Group A.
Keywords: pharyngitis, Streptococcus group A, McIsaac score, Rapid Antigen Detection Test